Alat Pengolah Air Tanah Menjadi Air Bersih dengan Proses Kombinasi Aerasi-Filtrasi Upflow (Desain Rancang Bangun) - Sri Indra Trigunarso; Rifai Agung Mulyono; Riyanto Suprawihadi (Jurnal Kesehatan, 2019)
In areas that have not received clean water services, residents usually use well water, river water which sometimes even often the water used does not meet the standards of healthy clean water. To treat well water/ ground water is usually the community. build a processing unit in the form of a sand filter. The problem that is often encountered in treatment is cleaning the filter media. This condition is often difficult for the community to do because it requires time and energy, resulting in the sand filter that is supposed to be operational continuously and finally stops and is not even used at all. To overcome this problem, it can be done by improving the design of water treatment units with a system of combination of aeration and upflow flow filtration. This study is to determine the ability of the tool to improve the quality of shallow groundwater in terms of turbidity, Fe, Mn, color and odor to clean water and saturation point of filtering. Research Design is a "quasi-experiment" in the form of "Time Series Design" using a "pre and post test" design without control. The tool is designed in the form of an application prototype to determine its ability to reduce turbidity, Fe, Mn, color and odor and the length of saturation point. The results showed that iron content before processing 2.12 after processing 2,058. pre-treatment manganese content 0.080 after processing 0.078. Color and smell before color processing and odor after processing are colorless and odorless. Microbiological quality for stool coly before processing week 1 32 after treatment 0, week 2 coly of feces before processing 26 after processing 0 and weeks 3 coly of feces before processing 21 and after processing 0. Length of processing up to saturation point filter media total contact time processing is 30 minutes.